Studi Pengaruh Kejadian Hujan Terhadap Banjir Lahar Di Sungai Gendol Menggunakan SIMLAR: Study Of The Effect Of Rain Incidence On Debris Flow In The Gendol River Using SIMLAR - Jazaul Ikhsan; Azqia Dara Adam; Ani Hairani (Media Ilmiah Teknik Sipil, 2023)
Indonesia is a country with the largest number of active volcanoes in the world and has the potential to erupt. This causes primary and secondary disasters, one of which is secondary disasters caused by lava floods during heavy rains. So disaster mitigation is needed by simulating lava floods to find out the predictions of speed, volume, height and area affected by lava floods. The simulation was carried out using SIMLAR software, carried out on Gendol River which is one of the watersheds that has the threat of lahar flooding. The test was carried out with 3 hyetograph patterns and for each pattern there were 3 simulations with different rainfall intensities, namely 162 mm, 243 mm and 324 mm. From these tests, the speed values ​​in patterns 1, 2 and 3 increased each simulation to the existing simulation. The speed value obtained by pattern 1 at 162 mm rain intensity is 2.35 m/s, at 243 mm rain intensity is 2.48 m/s, and at 324 mm rain intensity is 2.58 m/s. In addition, at high yields, volume and area also increase in each simulation due to the higher rainfall intensity. This proves that the intensity of rain is directly proportional to speed, volume, area and height. In addition, the hyetograph pattern also affects the peak hours when the maximum volume, maximum height and maximum speed are reached.